Consumer valuation of steaks with different quality attributes - Feldkamp, T.; Lusk, J.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Determining needs and wants of consumers is important for the beef industry to reverse the downward trend in beef demand during the last two decades. This study used experimental auctions in conjunction with a survey to determine consumer preferences for beef steaks. Four experimental auctions were used to elicit consumers’ maximum willingness to pay for five steak types: generic, guaranteed tender, “natural”, USDA Choice, and Certified Angus Beef (CAB). Consumers indicated flavor and tenderness were the most important factors when eating steaks, but they believed there was only about a 50% chance a generic steak would adequately meet these criteria. Though some concern was shown for the safety of meat produced with growth hormones and oral antibiotics, less than half of the consumers in this study were willing to pay more for a “natural” steak than a generic steak. Participants were willing to pay substantially more for guaranteed tender, USDA Choice, and CAB steaks.
Keywords: Beef; CAB steaks; USDA choice; Quality